(untitled) (Research, Society and Development, 2023)
Currently there are several options for oral rehabilitation in edentulous patients. An option already validated in the literature by several studies and which has been an alternative to the use of these grafts for oral rehabilitation is the total implant-supported rehabilitation protocol called All-on-four. This technique, initially published in 2003, has been proving to be a favorable option over the last two decades, as it is a fast and safe technique for complete dentate patients. The aim of this study was to present a literature review and a clinical case report of a patient with an atrophic maxilla, using the All-on-four protocol and rehabilitating with an implant-supported prosthesis. For this study, articles were searched in the PUBMED, Lilacs and Scielo databases. Articles were searched with the terms dental implants, oral rehabilitation, dental prosthesis planning and All-on-four protocol, in Portuguese and/or English. 34 articles published between 2003 and 2021 were selected. In addition, a clinical case was reported where this type of technique was chosen for rehabilitation. The All-on-four protocol has been advancing in the clinical and research areas, showing excellent success rates, numerous advantages and a high rate of acceptance by patients. The present clinical case pointed to a protocol for rapid execution, and with success in terms of aesthetics and function. It is concluded that this technique is a viable method especially for edentulous mandibles. Within the limits of this case report, it can be concluded that the All-on-four technique can be considered an alternative to rehabilitation with implants.